2010
DOI: 10.1002/srin.200900126
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Austenite Recrystallization by Comparing Double Deformation and Stress Relaxation Tests

Abstract: A high amount of deformation below the non-recrystallization temperature (T nr ) is a common industrial practice to achieve a good combination of toughness and strength in microalloyed steels. To combine the industrially relevant optimum combination of high productivity and product quality, an accurate knowledge of T nr and the recrystallization kinetics is required. Although a lot of literature data is available on the recrystallization behaviour of microalloyed steels, correlations are often difficult to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
4
19
0
Order By: Relevance
“…Note that the latter slopes might serve as an accurate parameter for assessing the recrystallisation fraction in hot-rolled steels. This possibility must be confirmed using mechanical methods, such as double-hit and stress-relaxation tests [67].…”
Section: Effect Of Frt On the  Conditioningmentioning
confidence: 99%
“…Note that the latter slopes might serve as an accurate parameter for assessing the recrystallisation fraction in hot-rolled steels. This possibility must be confirmed using mechanical methods, such as double-hit and stress-relaxation tests [67].…”
Section: Effect Of Frt On the  Conditioningmentioning
confidence: 99%
“…The most recent applications of this method include steel 300M [8] and steel GCr 15 [9]. Authors of the paper [10] compared stress relaxation and 2 step deformation methods and concluded that stress relaxation tests are less effective in determining the recrystallization behaviour of microalloyed steels. First of all, a very difficult and precise setup and control of the temperature and the deformation system is necessary.…”
Section: Niejednorodność Odkształcenia W Identyfikacji Modelu Rozwojumentioning
confidence: 99%
“…Finally, the resulting recrystallization kinetics cannot be compared with results from double deformation. In [10] accelerated kinetics was found when the stress relaxation method was used. Among the several methods developed to determine the fractional softening obtained from double deformation tests, there are two which better separate the effect of recovery and are thus more suitable to describe at an elevated temperature.…”
Section: Niejednorodność Odkształcenia W Identyfikacji Modelu Rozwojumentioning
confidence: 99%
See 1 more Smart Citation
“…Using different interpass times the softening kinetics can be evaluated. However, no indications about the recrystallized microstructure evolution can be gathered with indirect methods as DH, therefore direct observations have to be carried out [8][9][10].…”
Section: Introductionmentioning
confidence: 99%